Association Between Trichoscopic Features and Serum Hormone Levels and Vitamin D Concentration in Patients with Androgenetic Alopecia in Eastern China: A Cross-Sectional Study - Chen Q; Tao Q; Zhu Q; Zhu J; Du X (Clinical, Cosmetic and Investigational Dermatology, 2023)
Qitao Chen, Qiuwei Tao, Qilin Zhu, Jing Zhu, Xufeng Du Department of Dermatology, The Affiliated Wuxi People’s Hospital of Nanjing Medical University, Wuxi People’s Hospital, Wuxi Medical Center, Nanjing Medical University, Wuxi, People’s Republic of ChinaCorrespondence: Xufeng Du, Department of Dermatology, The Affiliated Wuxi People’s Hospital of Nanjing Medical University, Wuxi People’s Hospital, Wuxi Medical Center, Nanjing Medical University, No. 299 Qingyang Road, Wuxi, People’s Republic of China, Tel +86 19952290906, Email docdxf@126.comPurpose: Androgenetic alopecia (AGA) is a common dermatological condition, with reported associations between serum vitamin D and sex hormone levels. However, the relationship between these factors and the severity of hair loss remains unclear.Patients and Methods: Our cross-sectional study included 310 AGA patients who visited the dermatology clinic and underwent trichoscopy examinations throughout 2021. We collected data on serum sex hormones and 25(OH)D levels during their consultations. TrichoScan analysis was used to characterize and quantify AGA severity based on hair density and vellus hair proportions in the central scalp area, which were then correlated with the collected indicators.Results: The study findings reflect the basic demographic characteristics of AGA patients in the Chinese population. We discovered a significant negative correlation between serum SHBG levels and AGA severity in women, but no association was found in men. Serum testosterone, estradiol, dehydroepiandrosterone sulfate, and 25(OH)D levels showed no significant correlation with the severity of androgenetic alopecia, regardless of gender.Conclusion: To our knowledge, this is the first study to investigate the relationship between serum sex hormones, vitamin D, and AGA severity using trichoscopic scalp hair features.Keywords: androgenetic alopecia, TrichoScan, vitamin D, sex hormones